2021
DOI: 10.1021/jacs.1c03126
|View full text |Cite
|
Sign up to set email alerts
|

Site-Selective Defluorinative sp3 C–H Alkylation of Secondary Amides

Abstract: A site-selective defluorinative sp3 C–H alkylation of secondary amides that rapidly and reliably incorporates gem-difluoroalkene motifs into previously unfunctionalized sp3 sites is disclosed. This protocol is distinguished by its mild conditions, wide scope, and exquisite site-selectivity, thus unlocking a new platform to introduce carbonyl isosteres at saturated hydrocarbon sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(55 citation statements)
references
References 65 publications
0
55
0
Order By: Relevance
“…Pan independently reported the same reaction using 4CzIPN as the photocatalyst [73]. Interestingly, Martin found that the site selectivity of difluoroallylation switched from the δ-C-H bond of amides to the α-position when catalytic amounts of NiBr2•diglyme and 5,5′-dimethyl 2,2′-bipyridine were added (Scheme 29) [72]. The formation of an intermediate A by binding Ni(II) precatalyst to the oxygen site of amide was the reason for the activation of the α-C-H bond.…”
Section: Trifluoromethyl Alkenesmentioning
confidence: 97%
See 1 more Smart Citation
“…Pan independently reported the same reaction using 4CzIPN as the photocatalyst [73]. Interestingly, Martin found that the site selectivity of difluoroallylation switched from the δ-C-H bond of amides to the α-position when catalytic amounts of NiBr2•diglyme and 5,5′-dimethyl 2,2′-bipyridine were added (Scheme 29) [72]. The formation of an intermediate A by binding Ni(II) precatalyst to the oxygen site of amide was the reason for the activation of the α-C-H bond.…”
Section: Trifluoromethyl Alkenesmentioning
confidence: 97%
“…The hydrolysis of enamine F regenerated organocatalyst Cy2NH and uncovered the carbonyl group. Regioselective difluoroallylation of remote inactivated C(sp 3 )-H bond in amides was developed via an intramolecular 1,5-HAT process (Scheme 28) [72]. Martin disclosed the δ-C-H difluoroallylation of secondary trifluoroacetamides with α-trifluoromethyl styrenes using Ir(dFCF3ppy)2(dtbbpy)PF6 as the photocatalyst.…”
Section: Trifluoromethyl Alkenesmentioning
confidence: 99%
“…This defluorinative functionalization protocol set the stage for the introduction of gem-difluoroalkene motifs into α-amino C(sp 3 )-H sites. Interestingly, substrates having a trifluoromethyl group on the amide backbone enabled the functionalization of δ C(sp 3 )-H bonds under slightly modified reaction conditions with exclusion of the nickel catalyst (Scheme 36) [113].…”
Section: Allylationmentioning
confidence: 99%
“…An underexplored opportunity to achieve C(sp) 3 trifluoromethylation is the direct hydroalkylation of trifluoromethyl-substituted olefins. Specifically, the carbofunctionalization of these electrophilic unsaturated systems occurs readily at room temperature with exquisite functional group compatibility, 16 thus rendering the incorporation of pharmaceutically relevant cores and complex alkyl fragments feasible in a library setting. However, given the established propensity of trifluoromethyl-substituted alkenes to undergo intramolecular E1cB-type fluoride elimination in metal-catalyzed cross-couplings that proceed through the intermediacy of α-CF 3 -metal species 17 via the nucleophilic addition of organometallic reagents 18,19 or in the presence of traditional photoredox catalysts irrespective of the nature of the radical precursor ( Scheme 1B ), 16,19 a ,20 hydrofunctionalization 21 efforts remain challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the carbofunctionalization of these electrophilic unsaturated systems occurs readily at room temperature with exquisite functional group compatibility, 16 thus rendering the incorporation of pharmaceutically relevant cores and complex alkyl fragments feasible in a library setting. However, given the established propensity of trifluoromethyl-substituted alkenes to undergo intramolecular E1cB-type fluoride elimination in metal-catalyzed cross-couplings that proceed through the intermediacy of α-CF 3 -metal species 17 via the nucleophilic addition of organometallic reagents 18,19 or in the presence of traditional photoredox catalysts irrespective of the nature of the radical precursor ( Scheme 1B ), 16,19 a ,20 hydrofunctionalization 21 efforts remain challenging. In particular, the hydroalkylation of trifluoromethyl-substituted alkenes using unactivated alkyl counterparts presents a formidable, yet potentially powerful scenario to rapidly access unprecedented benzylically trifluoromethylated building blocks from commodity radical progenitors with a high content of C(sp 3 ) carbons.…”
Section: Introductionmentioning
confidence: 99%